(untitled) (Herald of the National Children’s Medical Center, 2025)
Acute Respiratory Distress Syndrome (ARDS) In newborns with congenital heart defects (CHD), it is a severe and life-threatening complication of the postoperative period. It significantly worsens the clinical prognosis, requiring effective and gentle respiratory support methods. One of the promising approaches is high-frequency oscillatory ventilation, which allows achieving adequate gas exchange with minimal barotrauma.